Identification of galactose‐α‐1, 3‐galactose in the gastrointestinal tract of the tick Ixodes ricinus; possible relationship with red meat allergy. Issue 4 (18th February 2013) - Hamsten, C.; Starkhammar, M.; Tran, T. A. T.; Johansson, M.; Bengtsson, U.; Ahlén, G.; Sällberg, M.; Grönlund, H.; van, M.
Abstract Patients with IgE antibodies against the carbohydrate epitope galactose‐α‐1, 3‐galactose (α‐Gal) have reported severe allergic reactions after consumption of red meat. Investigations have revealed associations between IgE to α‐Gal and tick bites. We provide the first direct evidence that α‐Gal is present within ticks thus potentially explaining the relationship between tick exposure and sensitization to α‐Gal, with development of red meat allergy as a secondary phenomena. Serum from Swedish patients with delayed severe reactions to red meat was included in the study. A dose‐dependent inhibition of IgE responses to α‐Gal by the tick Ixodes ricinus is demonstrated. Furthermore, using cryostat‐cut sections of I. ricinus, we show that both a monoclonal and a polyclonal antibody against α‐Gal stains the gastrointestinal tract of the tick. The same pattern is seen when staining with patient sera IgE positive to α‐Gal. These results confirm that the α‐Gal epitope is present in I. ricinus and imply host exposure to α‐Gal during a tick bite. This provides further evidence that tick bites are associated with IgE responses to α‐Gal and red meat allergy.